Dorothy Dale at Glenwood School - Penrose, Margaret; Nuttall, Charles, 1872-1934 (Salt Lake City, UT : Project Gutenberg, 2010)
"Dorothy Dale at Glenwood School" by Margaret Penrose is a fictional novel written in the early 20th century. The story revolves around the main character, Dorothy Dale, a spirited girl navigating her new circumstances following the death of her wealthy uncle in India, which has opened the door to new possibilities for her family. The novel captures her relationship with her best friend Tavia Travers, as they embark on adventures intertwined with themes of friendship, wealth, and personal growth. The opening of the book introduces us to Dorothy and her father, Major Dale, who happily discuss the unexpected inheritance and its potential for their life changes. Tavia, Dorothy's lively friend, soon arrives to join in the excitement, leading to lighthearted banter about hats and dreams of new adventures. However, beneath the joyous surface lie hints of tension, particularly as Dorothy faces the repercussions of past encounters with Andew Anderson, the source of her troubles. This first chapter sets the stage for a story rich in youthful camaraderie, budding worries about the future, and the impending transition to Glenwood School. (This is an automatically generated summary.)
Release date is 2010-08-24
Produced by Al Haines
Keywords: Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Girls -- Societies and clubs -- Juvenile fiction; Boarding school students -- Juvenile fiction; Teasing -- Juvenile fiction